2004
DOI: 10.1038/sj.onc.1208289
|View full text |Cite
|
Sign up to set email alerts
|

Parp-1 deficiency causes an increase of deletion mutations and insertions/rearrangements in vivo after treatment with an alkylating agent

Abstract: Accumulated evidence suggests that Parp-1 is involved in DNA repair processes, including base excision repair, single-strand and double-strand break repairs. To understand the precise role of Parp-1 in genomic stability in vivo, we carried out mutation analysis using Parp-1 knockout (Parp-1 À/À ) mice harboring two marker genes, gpt and red/gam genes. Spontaneous mutant frequencies of both genes in the bone marrows and livers did not differ significantly between Parp-1 À/À and Parp-1 þ / þ mice (P>0.05). After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 56 publications
3
40
0
Order By: Relevance
“…No significant differences in spontaneous MFs were reported in p53, Atm or Parp-1 knockout gpt delta mice, although heavy-ion or X-ray irradiation induced more large deletions in knockout mice than in wild type mice. 17,21,26) In the gpt delta rat, the spontaneous Spi − MFs we have obtained from 13 rat tissues were between 1.3 × 10 −6 and 4.4 × 10 −6 , similar to those observed in gpt delta mice. 12) No marked strain difference has been observed between SD and F344 rats although additional studies are needed to confirm this finding.…”
Section: Spi − Assay (Spi − Selection) For Deletionssupporting
confidence: 48%
See 1 more Smart Citation
“…No significant differences in spontaneous MFs were reported in p53, Atm or Parp-1 knockout gpt delta mice, although heavy-ion or X-ray irradiation induced more large deletions in knockout mice than in wild type mice. 17,21,26) In the gpt delta rat, the spontaneous Spi − MFs we have obtained from 13 rat tissues were between 1.3 × 10 −6 and 4.4 × 10 −6 , similar to those observed in gpt delta mice. 12) No marked strain difference has been observed between SD and F344 rats although additional studies are needed to confirm this finding.…”
Section: Spi − Assay (Spi − Selection) For Deletionssupporting
confidence: 48%
“…The gpt and Spi − assay systems have been validated primarily in mice with many chemical mutagens/carcinogens, UV and ionizing radiation, for which mutagenicity, organ specificity and mutation spectrum have been thoroughly characterized. 1,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Recently, the outbred gpt delta SD rat was backcrossed with Fisher 344 (F344) rat, to establish an inbred gpt delta rat (F344). In this review, we focus on the spontaneous mutations detected by the gpt and Spi − assays in gpt delta mice and rats and discuss possible mechanisms underlying these in vivo mutations.…”
Section: Overview Of Gpt Delta Transgenic Rodentsmentioning
confidence: 99%
“…Recent studies using PARP-1 mutant mice have implicated PARP-1 in the suppression of tumorigenesis (Tong et al, 2001a;Masutani et al, 2003). Although PARP-1À/À mice develop spontaneous tumors at a low incidence (Tong et al, 2002), they are susceptible to chemical carcinogeninduced tumorigenesis, with increased mutation rates (Tsutsumi et al, 2001;Nozaki et al, 2003;Shibata et al, 2005). Inactivation of PARP-1 has been shown to result in a high frequency of T-cell lymphomas in severe combined immunodeficiency mice (Morrison et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In support of this hypothesis, it has recently been reported that the genomes of PARP-1 null mice show an increased incidence of deletion mutations upon DNA damage (Shibata et al, 2005).…”
Section: Poly(adp-ribose)polymerasementioning
confidence: 56%